Study of Integrated Wooden Agroindustry Development in The Village of Watondo, Tongkuno, South District Muna District - Awi, La; Rianda, La; Herdhiansyah, Dhian (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the development of integrated cassava agroindustry in Watondo Village, South Tongkuno District, Muna Regency. The population in this study is integrated cassava agroindustry, the selection of samples using the sense method with 23 respondents classified in 3 categories namely having cassava plantations without agroindustry business with 7 respondents, having cassava plantations and owning an agroindustry business with 11 respondents, having an agro-industry business without cassava plantation with 5 respondents. Data collection is done by interview method, questionnaire, documentation. Data analysis uses income analysis and Comparative performance index analysis. The results showed the highest average income results in the three types of businesses, having an agro-industry business without cassava plantation with income in 2017 of Rp 18,366,850, in 2018 amounting to Rp 23,081,883, CPI analysis with a value of 232,434, owning garden cassava, and having an agro-industry business with income in 2017 amounting to Rp 10,130,894, in 2018 amounting to Rp 12,036,159 CPI analysis with a value of 130,403, and for business types, having cassava plantations without agro-industry businesses with income in 2017 of Rp. 6,984,905, in 2018 amounting to 9,477,679, CPI analysis with a value of 100.